Development of IoT Based Clothesline using Microcontroller - Zulkipli, Muhammad Asyraf; Yusof, Khairul Huda; sani, Almadora Anwar; Herizal, Muhammad Auzi (International Journal of Mechanics, Energy Engineering and Applied Science (IJMEAS), 2023)
Sunlight has long been used in daily activities, especially drying clothes. The only concern is sudden rain and people are not aware that their clothes are still on the clothesline. Due to this, many opt to dry their clothes indoor, which takes longer to dry. With regard to the aforementioned issue, in this research, Internet of Things (IoT) concept is applied in the production of automatic clotheslines by the integration of weather monitoring and forecasting with automatic clothesline. This automatic clothesline has an LDR sensor and a rain sensor to detect light and raindrops in the environment, then the values obtained from these two sensors are processed by the microcontroller to control the DC motor that can moves the clothes inside and outside from the sensors system which can be monitored and controled via smartphone using the Blynk app. The outcome of this research is an automatic clothesline prototype that is accessible through the Blynk app; utilising LDR sensors, rain sensors, and motor to retrieve clothes.